Deletion rescue resulting in segmental homozygosity: A mechanism underlying discordant NIPT results. Issue 11 (15th August 2020) - Caldwell, Samantha; Sagaser, Katelynn; Nelson, Zoe; Frey, Jennifer; Wardrop, Jenna; Boomer, Theresa; McCullough, Ron; Schwartz, Stuart
Abstract: With the increasing capabilities of non‐invasive prenatal testing (NIPT), detection of sub‐chromosomal deletions and duplications are possible. This case series of deletion rescues resulting in segmental homozygosity helps provide a biological explanation for NIPT discrepancies and adds to the dearth of existing literature surrounding segmental UPD cases and their underlying mechanisms. In the three cases presented here, NIPT reported a sub‐chromosomal deletion (in isolation or as part of a complex finding). Diagnostic testing, however, revealed segmental homozygosity or UPD for the region reported deleted on NIPT. Postnatal placental testing was pursued in two cases and confirmed the NIPT findings. This discordance between the screening and diagnostic testing is suggestive of a corrective post‐zygotic event, such as telomere capture and/or deletion rescue, ultimately resulting in segmental homozygosity and fetoplacental mosaicism. Imprinted chromosomes and autosomal recessive disease genes make homozygosity an important clinical consideration. Amniocentesis with SNP microarray is particularly useful in determining both copy number and UPD issues alike.